Personal security in travel by public transport: the role of traveller information and associated technologies. Issue 2 (1st March 2015) - Beecroft, Mark; Pangbourne, Kate
Abstract : This study focuses on the role of traveller information and associated technologies in supporting personal security in travel by public transport. It reports research undertaken via a workshop involving SWOT analysis and scenario planning and a series of expert interviews. These research activities created a baseline understanding of how personal security issues are currently addressed, and identified potential future issues and how they might be tackled. Information is a major source of confidence and reassurance when travelling and can greatly support perceptions of personal security in travel. There have been significant advances in recent years in the quantity of information available and in delivery mechanisms. However, significant issues remain, particularly in terms of information quality, its representation in the public realm and its ability to support the needs of users. The differences in the relationship between information requirements and related commercial imperatives is shown to be perhaps the critical factor in determining the alternative pathways and associated services, technologies and personal security outcomes which emerge under the different scenarios.